Learning how to manage the boundaries between life domains: effects of a boundary management intervention on boundary management, recovery, and well-being - Rexroth, Miriam; Feldmann, Elisa; Peters, Anna; Sonntag, Karlheinz (Zeitschrift für Arbeits- und Organisationspsychologie, 2016)
Abstract. To evaluate the effects of a boundary management intervention on boundary management, recovery experiences, and well-being variables, we conducted a quasi-experimental study using an intervention lasting two consecutive days. The sample consisted of 64 employees of a large international German company; 37 in the experimental group and 27 in the control group. Boundary management, recovery experiences, and well-being outcomes were measured before the intervention and 2 weeks after the intervention. Analyses of covariance revealed an increase in boundary creation and detachment, but, contrary to the hypothesis, a decrease in control during leisure time after the intervention. No effects were found for the well-being variables.
Gesehen am 18.04.2017